2001
DOI: 10.1006/excr.2001.5161
|View full text |Cite
|
Sign up to set email alerts
|

Direct Inhibition of Indian Hedgehog Expression by Parathyroid Hormone (PTH)/PTH-Related Peptide and Up-Regulation by Retinoic Acid in Growth Plate Chondrocyte Cultures

Abstract: Indian hedgehog (Ihh) is highly expressed in prehypertrophic chondrocytes in vivo and has been proposed to regulate the proliferation and maturation of chondrocytes and bone collar formation in the growth plate. In high-density cultures of rabbit growth-plate chondrocytes, Ihh mRNA was also expressed at the highest level in the prehypertrophic stage. To explore endogenous factors that regulate Ihh expression in chondrocytes, we examined the effects of various growth factors on Ihh mRNA expression in this syste… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
28
1
1

Year Published

2001
2001
2016
2016

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 44 publications
(34 citation statements)
references
References 42 publications
4
28
1
1
Order By: Relevance
“…Several mechanisms, including those involving Runx-2, bone morphogenetic proteins (BMPs), retinoic acid, and the Erk and p38 MAP kinases have been shown to activate Ihh transcription (Yoshida et al, 2004(Yoshida et al, , 2001Seki and Hata, 2004;. Rapamycin did not affect Runx2 expression in our studies.…”
Section: Discussioncontrasting
confidence: 50%
“…Several mechanisms, including those involving Runx-2, bone morphogenetic proteins (BMPs), retinoic acid, and the Erk and p38 MAP kinases have been shown to activate Ihh transcription (Yoshida et al, 2004(Yoshida et al, , 2001Seki and Hata, 2004;. Rapamycin did not affect Runx2 expression in our studies.…”
Section: Discussioncontrasting
confidence: 50%
“…Yoshida et al [2001] first demonstrated this in primary chicken chondrocytes showing that PTH directly down-regulated Ihh mRNA levels, independent of its effect on differentiation. Ihh regulation was mimicked by a cAMP analog and was not blocked by either cycloheximide or actinomycin D, suggesting that PTH directly inhibits Ihh gene transcription, possibly via the cAMP/PKA pathway.…”
Section: Inhibitors Of Ihh Expressionmentioning
confidence: 93%
“…Retinoic acid (RA) has also been reported to increase Ihh levels in chondrocytes [Yoshida et al, 2001]. Yoshida et al first demonstrated in primary chicken chondrocytes that RA increased Ihh transcription in a process that required de novo protein synthesis.…”
Section: Stimulators Of Ihh Expressionmentioning
confidence: 99%
“…) are divergent members of the Indian subgroup (green). Fan and Tessier-Lavigne 1994;Johnson et al 1994;Chiang et al 1996;Teillet et al 1998;Murtaugh et al 1999;Zhang et al 2001 Ihh Coordination of proliferation/ differentiation in endochondral skeleton Lankse et al 1996;Vortkamp et al 1996;St-Jacques et al 1999;Enomoto-Iwato et al 2000;Karp et al 2000;Chung et al 2001;Long et al 2001;Yoshida et al 2001 Cement gland induction…”
mentioning
confidence: 99%